Four-channel Control of Master-slave Robotic System with User’s Force Transfer during Obstacle Collision at the Remote Site based on Input-to-state Stability - Mohammad Reza Satvati; Hossein Karimpour; Keivan Torabi; Mohammad Motaharifar (هوش محاسباتی در مهندسی برق)
The possibility of transferring the sense and force of the user on the driver side to the follower robot has always been discussed in master/slave systems. It has gained special importance in recent research. In the present study, the control torque of the slave side is adjusted by transferring the user's force (with the haptic handle) from the master side to the slave robot. The proposed system is a four-channel approach where the position signal and force signal are transmitted to the slave on the master's side, and reciprocally, the position signal and the contact force of the environment on the slave reach the master's side. The input-to-state stability for the master-slave system is investigated with the proposed approach. The approach of this research, unlike the approach of many previous studies, does not require the acceleration of the joints to parameterize the robot's dynamics or control it. In this method, the amount of force/torque of the user's hand of the master robot will be directly involved in the control command of the slave robot. In this article, in addition to the four-channel system, a three-channel system is proposed. Both systems, in addition to following the path, can follow the user's will on the master's side when encountering unexpected obstacles and stopping joints. In addition to software simulation, experimental implementation has been done on a leader-follower system with haptic robots, which confirms the correctness of the proposed approach.